From leaves to seeds? The dietary shift in late Miocene colobine monkeys of southeastern Europe. (1st August 2021) - Thiery, Ghislain; Gibert, Corentin; Guy, Franck; Lazzari, Vincent; Geraads, Denis; Spassov, Nikolai; Merceron, Gildas
Abstract: Extant colobine monkeys are specialized leaf eaters. But during the late Miocene, western Eurasia was home to colobines that were less efficient at chewing leaves than they were at breaking seed shells. To understand the link between folivory and granivory in this lineage, the dietary niche of Mesopithecus delsoni and Mesopithecus pentelicus was investigated in southeastern Europe, where a major environmental change occurred during the late Miocene. We combined dental topographic estimates of chewing efficiency with dental microwear texture analysis of enamel wear facets. Mesopithecus delsoni was more efficient at chewing leaves than M. pentelicus, the dental topography of which matches an opportunistic seed eater. Concurrently, microwear complexity increases in M. pentelicus, especially in the northernmost localities corresponding to present‐day Bulgaria. This is interpreted as a dietary shift toward hard foods such as seeds or tubers, which is consistent with the savanna and open mixed forest biomes that covered Bulgaria during the Tortonian. The fact that M. delsoni was better adapted to folivory and consumed a lower amount of hard foods than M. pentelicus suggests that colobines either adapted to folivory before their dispersal to Europe or evolved adaptations to leaf consumption in multiple occurrences.